Specifics of joint ownership of land, according to Ukraine’s laws - Paslavskа, Olha (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
In the article was performed scientific research of specifics for legislative management for real estate joint ownership, which occurs between regular citizens and companies, governments and communities